2021
DOI: 10.3389/fendo.2021.793621
|View full text |Cite
|
Sign up to set email alerts
|

Follicular GH and IGF1 Levels Are Associated With Oocyte Cohort Quality: A Pilot Study

Abstract: IntroductionOocyte quality contributes to the development of an optimal embryo and thus a successful pregnancy. The objective of this study was to analyse the association between oocyte cohort quality and the follicular levels of growth hormone (GH), insulin-like growth factor 1 (IGF1), 25-hydroxy vitamin D (25OHD), thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), free thyroxine (fT4) and antithyroid antibodies, as a function of intracytoplasmic sperm injection (ICSI) outcomes.Material and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The median age was 35.5 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Group-I, 29.5 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) in Group-II, and 33.0 in Group-III, and the difference between the groups was statistically significant (p<0.001). The mean BMI was 23.55 in Group-I, 23.1 in Group-II, and 24.0 in Group-III (p=0.751).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The median age was 35.5 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in Group-I, 29.5 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) in Group-II, and 33.0 in Group-III, and the difference between the groups was statistically significant (p<0.001). The mean BMI was 23.55 in Group-I, 23.1 in Group-II, and 24.0 in Group-III (p=0.751).…”
Section: Resultsmentioning
confidence: 96%
“…However, it has no direct relation with OR; the possible positive effect on ovarian response may be related with proliferation and differentiation of granulosa cells by IGF-1. A pilot study published recently investigated the relationship between oocyte quality and follicular GH and IGF-1 levels 30 . The results show that levels of GH and IGF1 were higher in the normal oocyte cohort than in the abnormal oocyte cohort.…”
Section: Discussionmentioning
confidence: 99%
“…GH is more frequently applied as an adjuvant reagent during fertility treatment, and the results from studies using animal and human models demonstrate that GH and IGF-1 are important intraovarian regulators of steroidogenesis, cell proliferation, and follicular development ( 42 ). Indeed, a prospective comparative pilot study showed that the follicular levels of GH and IGF-1 are higher in the corresponding oocytes with a normal morphology ( 80 ), indicating a correlation of follicular fluid GH/IGF-1 levels with oocyte quality. In dairy cows, intraovarian IGF-1 injection increases the cell number of the inner cell mass (ICM) during the morula to blastocyst transition of the embryos, indicating a regulatory role of IGF-1 in embryo development ( 81 ).…”
Section: Growth Hormone In the Female Reproductive Systemmentioning
confidence: 99%
“…Another study also found a positive correlation between follicular IGF-1 and the number of matured oocytes ( 102 ). With regard to oocyte quality, a recent prospective pilot study found that the follicular fluid levels of GH and IGF-1 were higher in the normal oocyte cohort than in the abnormal oocyte cohort (more than 50% of oocytes presented at least one morphological abnormality), indicating a positive correlation between the follicular fluid levels of GH and IGF-1 and oocyte quality ( 80 ). Additionally, this study also demonstrated that the fertilization rate was higher in the normal oocyte cohort than in the abnormal oocyte cohort ( 80 ).…”
Section: Growth Hormone and Human Oocyte Qualitymentioning
confidence: 99%
See 1 more Smart Citation